Electrolyte diffusion coefficient testing device

CN224839785UActive Publication Date: 2026-10-09CONTEMPORARY AMPEREX TECHNOLOGY CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202522144712.7
Authority / Receiving Office
CN · China
Patent Type
Utility models(China)
Current Assignee / Owner
Filing Date
2025-10-10
Publication Date
2026-10-09
Estimated Expiration
2035-10-10

AI Technical Summary

Technical Problem

[0004]鉴于上述问题,本申请提供一种电解液扩散系数测试装置,能够解决测试装置在使用时,不能准确得到测量结果的问题

Benefits of technology

[0006]本申请实施例的技术方案中,将正极壳置于最底部,依次放入第二电极、隔膜,同时将环形绝缘层设置在隔膜朝向第二电极的一侧,之后在隔膜上滴入微量待测电解液,然后继续放入第一电极,再将负极壳扣合到正极壳上,最后将整体装置接入测试仪器,即可进行测试。整体装置结构简单。通过在隔膜朝向第二电极的一侧设置环形绝缘层,且环形绝缘层的外径大于或等于隔膜的外径,这样环形绝缘层就可以阻断粒子通过第一电极或第二电极的边缘传输,电流只能通过环形绝缘层中间限定的中心圆形区域进行传输,强制规整电流线分布。在中心圆形区域内,第一电极和第二电极之间平行相对,电流线变得近似垂直且分布高度均匀,电流密度从中心到边缘的差异被降到最低,消除了因三维扩散和路径长度差异造成的边缘效应,这样就可以准确得到测量结果。而且,由于隔膜为具有多孔迂曲结构的无纺布隔膜,能够延长锂离子的扩散路径和弛豫时间,这样使得整体测量过程更加接近电化学理论中的“半无限扩散”理想模型,此时,电压随时间变化的曲线变得更容易测量和分析,从而可以更准确、更方便地应用菲克扩散定律公式来拟合和计算出离子在电解液中的有效扩散系数,进一步提高了测量结果。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN224839785U_ABST
    Figure CN224839785U_ABST
Patent Text Reader

Abstract

The application discloses an electrolyte diffusion coefficient testing device, which comprises a negative electrode shell, a first electrode, a diaphragm, an annular insulating layer, a second electrode and a positive electrode shell. The application has the advantages that the overall device structure is simple, the annular insulating layer is arranged on the side of the diaphragm facing the second electrode, and the outer diameter of the annular insulating layer is greater than or equal to the outer diameter of the diaphragm, so that the annular insulating layer can block the transmission of particles through the edges of the first electrode or the second electrode, and the current can only be transmitted through the central circular area defined in the middle of the annular insulating layer, so that the current line distribution is forced to be regular. In the central circular area, the first electrode and the second electrode are parallel to each other, the current line becomes approximately vertical and is uniformly distributed, the difference in current density from the center to the edge is minimized, and the edge effect caused by three-dimensional diffusion and path length difference is eliminated, so that the measurement result can be accurately obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of battery testing technology, and in particular to an electrolyte diffusion coefficient testing device. Background Technology

[0002] As a core component of lithium-ion batteries, the electrolyte's internal ion transport characteristics, especially its liquid-phase diffusion coefficient, directly determine the battery's fast-charging and rate performance. To test the electrolyte's diffusion coefficient, a testing device is needed for measurement.

[0003] The testing devices in related technologies cannot accurately obtain measurement results during use. Utility Model Content

[0004] In view of the above problems, this application provides an electrolyte diffusion coefficient testing device, which can solve the problem that the testing device cannot accurately obtain measurement results during use.

[0005] To solve the above-mentioned technical problems, this application proposes an electrolyte diffusion coefficient testing device, comprising: a negative electrode shell, a first electrode, a diaphragm, an annular insulating layer, a second electrode, and a positive electrode shell; The negative electrode shell and the positive electrode shell are fastened together to form a receiving space. The first electrode, the diaphragm, and the second electrode are sequentially disposed in the receiving space along a first direction, wherein the first direction is the direction from the negative electrode shell to the positive electrode shell. The annular insulating layer is disposed on the side of the diaphragm facing the second electrode, and the outer diameter of the annular insulating layer is greater than or equal to the outer diameter of the diaphragm; The diaphragm is a nonwoven diaphragm with a porous tortuous structure, configured to extend the diffusion path and relaxation time of lithium ions.

[0006] In the technical solution of this application embodiment, the positive electrode shell is placed at the bottom, followed by the second electrode and the diaphragm. An annular insulating layer is placed on the side of the diaphragm facing the second electrode. A small amount of the electrolyte to be tested is then dripped onto the diaphragm. Next, the first electrode is placed, and the negative electrode shell is then attached to the positive electrode shell. Finally, the entire device is connected to a testing instrument for testing. The overall device structure is simple. By setting an annular insulating layer on the side of the diaphragm facing the second electrode, with the outer diameter of the annular insulating layer being greater than or equal to the outer diameter of the diaphragm, the annular insulating layer can block particle transmission through the edges of the first or second electrode. Current can only be transmitted through the central circular area defined by the annular insulating layer, forcibly regulating the current line distribution. Within the central circular area, the first and second electrodes are parallel and opposite each other, the current lines become approximately perpendicular and have a highly uniform distribution, and the difference in current density from the center to the edge is minimized, eliminating the edge effect caused by three-dimensional diffusion and path length differences. This allows for accurate measurement results. Moreover, since the diaphragm is a non-woven fabric diaphragm with a porous and tortuous structure, it can prolong the diffusion path and relaxation time of lithium ions. This makes the overall measurement process closer to the ideal model of "semi-infinite diffusion" in electrochemical theory. At this time, the curve of voltage change over time becomes easier to measure and analyze, so that Fick's diffusion law formula can be applied more accurately and conveniently to fit and calculate the effective diffusion coefficient of ions in the electrolyte, further improving the measurement results.

[0007] In some embodiments, the electrolyte diffusion coefficient testing device further includes an elastic element; the elastic element is disposed between the second electrode and the positive electrode shell.

[0008] In this way, the elastic force provided by the elastic element can make the components between the negative electrode shell and the positive electrode shell fit tightly together.

[0009] In some embodiments, the end of the elastic member facing the positive electrode shell is engaged with the positive electrode shell. This ensures that the elastic member is stably positioned on the positive electrode shell, preventing it from wobbling during use.

[0010] In some embodiments, the electrolyte diffusion coefficient testing device further includes a first conductive sheet and a second conductive sheet; The first conductive sheet is disposed between the negative electrode shell and the first electrode, and the second conductive sheet is disposed between the second electrode and the elastic member. In this way, by filling the corresponding receiving space with the first and second conductive sheets, the various components within the receiving space can be tightly fitted together.

[0011] In some embodiments, the first conductive sheet is a rigid conductive sheet, and / or the second conductive sheet is a rigid conductive sheet. This improves the corresponding support and effectively resists the effects of external vibrations during testing.

[0012] In some embodiments, when the inner diameter of the negative electrode shell is smaller than the inner diameter of the positive electrode shell, the diameter of the diaphragm is smaller than the inner diameter of the negative electrode shell, and the diameter of the diaphragm is larger than the diameter of the first electrode.

[0013] This ensures the stability of the diaphragm's position during the encapsulation process, preventing the diaphragm edges from curling due to pressure from the snap-fit ​​structure, which could cause electrochemical test results to deviate from theoretical values.

[0014] In some embodiments, the thickness of a single layer in the diaphragm is greater than 100 μm, and the total thickness of the diaphragm is greater than 400 μm and less than 800 μm.

[0015] This avoids situations where the total thickness of the membrane is too low, which would prevent the ion diffusion process from being accurately captured by electrochemical signals, thus affecting the measurement results.

[0016] In some embodiments, the porosity of the nonwoven membrane is 30%-45%.

[0017] Because the porosity of different batches of membranes varies greatly, it affects the transport rate of ions within the porous membrane, making direct comparison of data from different experiments impossible. By limiting the porosity, large differences in ion transport rates within the porous membrane can be avoided.

[0018] In some embodiments, the positive electrode shell has a recessed portion on the side facing the negative electrode shell, and when the negative electrode shell and the positive electrode shell are fastened together, the side of the negative electrode shell away from the positive electrode shell is located in the recessed portion.

[0019] This avoids the negative electrode shell protruding from the concave part, resulting in a smaller overall device size.

[0020] In some embodiments, the annular insulating layer is bonded to the side of the diaphragm facing the second electrode. This facilitates the connection of the annular insulating layer to the diaphragm.

[0021] The above description is only an overview of the technical solution of this application. In order to better understand the technical means of this application and to implement it in accordance with the contents of the specification, and to make the above and other objects, features and advantages of this application more obvious and understandable, the following are specific embodiments of this application. Attached Figure Description

[0022] Various other advantages and benefits will become apparent to those skilled in the art upon reading the detailed description of the embodiments described below. The accompanying drawings are for illustrative purposes only and are not intended to limit the scope of this application. Furthermore, the same reference numerals denote the same parts throughout the drawings. In the drawings: Figure 1 This is a schematic diagram of the structure of an electrolyte diffusion coefficient testing device provided in some embodiments of this application.

[0023] The reference numerals in the detailed embodiments are as follows: 10. Negative electrode shell; 11. First conductive sheet; 12. First electrode; 13. Separator; 14. Annular insulating layer; 15. Second electrode; 16. Second conductive sheet; 17. Elastic element; 18. Positive electrode shell; 181. Inner recess. Detailed Implementation

[0024] The embodiments of the technical solution of this application will now be described in detail with reference to the accompanying drawings. These embodiments are only used to more clearly illustrate the technical solution of this application and are therefore merely examples, and should not be used to limit the scope of protection of this application.

[0025] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application pertains; the terminology used herein is for the purpose of describing particular embodiments only and is not intended to limit the application; the terms “comprising” and “having”, and any variations thereof, in the specification, claims, and foregoing description of the drawings are intended to cover non-exclusive inclusion.

[0026] In the description of the embodiments of this application, technical terms such as "first" and "second" are used only to distinguish different objects and should not be construed as indicating or implying relative importance or implicitly specifying the number, specific order, or primary and secondary relationship of the indicated technical features. In the description of the embodiments of this application, "multiple" means two or more, unless otherwise explicitly defined.

[0027] In this document, the term "embodiment" means that a particular feature, structure, or characteristic described in connection with an embodiment may be included in at least one embodiment of this application. The appearance of this phrase in various places throughout the specification does not necessarily refer to the same embodiment, nor is it a separate or alternative embodiment mutually exclusive with other embodiments. It will be explicitly and implicitly understood by those skilled in the art that the embodiments described herein can be combined with other embodiments.

[0028] In the description of the embodiments in this application, the term "and / or" is merely a description of the relationship between related objects, indicating that three relationships can exist. For example, A and / or B can represent: A existing alone, A and B existing simultaneously, and B existing alone. Additionally, the character " / " in this document generally indicates that the preceding and following related objects have an "or" relationship.

[0029] In the description of the embodiments of this application, the term "multiple" refers to two or more (including two), similarly, "multiple sets" refers to two or more (including two sets), and "multiple pieces" refers to two or more (including two pieces).

[0030] In the description of the embodiments of this application, the technical terms "center," "longitudinal," "lateral," "length," "width," "thickness," "upper," "lower," "front," "rear," "left," "right," "vertical," "horizontal," "top," "bottom," "inner," "outer," "clockwise," "counterclockwise," "axial," "radial," and "circumferential" indicate the orientation or positional relationship based on the orientation or positional relationship shown in the accompanying drawings. They are only for the convenience of describing the embodiments of this application and simplifying the description, and are not intended to indicate or imply that the device or element referred to must have a specific orientation, or be constructed and operated in a specific orientation. Therefore, they should not be construed as limitations on the embodiments of this application.

[0031] In the description of the embodiments of this application, unless otherwise expressly specified and limited, technical terms such as "installation," "connection," "joining," and "fixing" should be interpreted broadly. For example, they can refer to a fixed connection, a detachable connection, or an integral part; they can refer to a mechanical connection or an electrical connection; they can refer to a direct connection or an indirect connection through an intermediate medium; they can refer to the internal communication of two components or the interaction between two components. For those skilled in the art, the specific meaning of the above terms in the embodiments of this application can be understood according to the specific circumstances.

[0032] As a core component of lithium-ion batteries, the electrolyte's internal ion transport characteristics, especially its liquid-phase diffusion coefficient, directly determine the battery's fast-charging and rate performance. Therefore, developing a device capable of accurately and conveniently testing electrolyte kinetic parameters is crucial for advancements in battery technology.

[0033] The testing devices in related technologies are complex in structure, cumbersome in assembly, and have poor consistency in testing conditions, which seriously restricts the accuracy and reliability of measurement results.

[0034] Based on the above considerations, in order to solve the problem that the test device cannot accurately obtain measurement results during use, an electrolyte diffusion coefficient test device was designed. The device includes a negative electrode shell, a first electrode, a separator, an annular insulating layer, a second electrode, and a positive electrode shell. The negative electrode shell and the positive electrode shell are fastened together to form a receiving space. The first electrode, the separator, and the second electrode are sequentially arranged in the receiving space along a first direction, which is the direction from the negative electrode shell to the positive electrode shell. The annular insulating layer is disposed on the side of the separator facing the second electrode, and the outer diameter of the annular insulating layer is greater than or equal to the outer diameter of the separator. The separator is a non-woven fabric separator with a porous tortuous structure, which is configured to prolong the diffusion path and relaxation time of lithium ions.

[0035] In the technical solution of this application embodiment, the positive electrode shell is placed at the bottom, followed by the second electrode and the diaphragm. An annular insulating layer is placed on the side of the diaphragm facing the second electrode. A small amount of the electrolyte to be tested is then dripped onto the diaphragm. Next, the first electrode is placed, and the negative electrode shell is then attached to the positive electrode shell. Finally, the entire device is connected to a testing instrument for testing. The overall device structure is simple. By setting an annular insulating layer on the side of the diaphragm facing the second electrode, with the outer diameter of the annular insulating layer being greater than or equal to the outer diameter of the diaphragm, the annular insulating layer can block particle transmission through the edges of the first or second electrode. Current can only be transmitted through the central circular area defined by the annular insulating layer, forcibly regulating the current line distribution. Within the central circular area, the first and second electrodes are parallel and opposite each other, the current lines become approximately perpendicular and have a highly uniform distribution, and the difference in current density from the center to the edge is minimized, eliminating the edge effect caused by three-dimensional diffusion and path length differences. This allows for accurate measurement results. Moreover, since the diaphragm is a non-woven fabric diaphragm with a porous and tortuous structure, it can prolong the diffusion path and relaxation time of lithium ions. This makes the overall measurement process closer to the ideal model of "semi-infinite diffusion" in electrochemical theory. At this time, the curve of voltage change over time becomes easier to measure and analyze, so that Fick's diffusion law formula can be applied more accurately and conveniently to fit and calculate the effective diffusion coefficient of ions in the electrolyte, further improving the measurement results.

[0036] According to some embodiments of this application, Figure 1 This is a schematic diagram of the electrolyte diffusion coefficient testing device in this application. Figure 1 As shown, this application provides an electrolyte diffusion coefficient testing device, which includes a negative electrode shell 10, a first electrode 12, a separator 13, an annular insulating layer 14, a second electrode 15, and a positive electrode shell 18. The negative electrode shell 10 and the positive electrode shell 18 are fastened together to form a receiving space. The first electrode 12, the separator 13, and the second electrode 15 are sequentially disposed in the receiving space along a first direction, wherein the first direction is the direction from the negative electrode shell 10 to the positive electrode shell 18. The annular insulating layer 14 is disposed on the side of the separator 13 facing the second electrode 15, and the outer diameter of the annular insulating layer 14 is greater than or equal to the outer diameter of the separator 13. The separator 13 is a non-woven fabric separator with a porous tortuous structure, configured to prolong the diffusion path and relaxation time of lithium ions.

[0037] In this embodiment, the first electrode 12 and the second electrode 15 can be lithium metal sheets, platinum metal sheets, etc., the diaphragm 13 can be a non-woven fabric diaphragm, and the annular insulating layer 14 can be insulating glue, insulating plastic film, etc. The specifics can be determined according to the actual situation, and this specification does not limit them in this embodiment.

[0038] In this embodiment, the structure of the negative electrode shell 10 and the positive electrode shell 18 fastening together is equivalent to the male / female snap fastener of a button cell battery. Assembly is completed simply by pressing the negative electrode shell 10 onto the positive electrode shell 18. Of course, it is understood that the negative electrode shell 10 and the positive electrode shell 18 can also be fastened together through a structure of protrusions and grooves. The specific fastening can be determined according to the actual situation, and this embodiment does not limit this.

[0039] In this embodiment, the inner diameter of the annular insulating layer 14 can be 14 mm and the outer diameter can be 20 mm. The diameter of the first electrode 12 and the second electrode 15 can be 19 mm. When the annular insulating layer 14 is attached to the side of the diaphragm 13 facing the second electrode 15, the annular insulating layer 14 can block the transmission of particles through the edge of the first electrode 12 or the second electrode 15. The current can only be transmitted through the central circular area defined in the middle of the annular insulating layer 14, thus forcibly regulating the distribution of current lines.

[0040] In this embodiment, the separator 13 is a non-woven fabric separator with a porous, tortuous structure. "Porous" refers to the numerous interconnected, tiny pores (cavities) within the separator. These pores can hold the electrolyte, providing transport channels for lithium ions. "Tortuous" describes the degree of tortuosity of the actual path ions take within this porous network. Ions cannot travel in a straight line from one side of the separator to the other. They must constantly navigate around the "walls" formed by the separator fibers, resulting in a winding and extremely tortuous path. In summary, a "porous, tortuous structure" is a solid medium filled with interconnected, tortuous micropores.

[0041] Because of its porous and tortuous structure, the actual path of ions is winding and non-linear, which forces ions to take a longer route, thereby extending the diffusion path of lithium ions.

[0042] Relaxation time refers to the time required for the ion concentration to recover from a non-uniform state to a uniform equilibrium state after a battery pulse charge / discharge. This recovery process mainly relies on diffusion. The relaxation time is directly proportional to the diffusion coefficient and the square of the diffusion distance. Because the diffusion path of lithium ions is lengthened, the corresponding relaxation time is also lengthened.

[0043] In the technical solution of this application embodiment, the positive electrode shell 18 is placed at the bottom, followed by the second electrode 15 and the diaphragm 13. An annular insulating layer 14 is then placed on the side of the diaphragm 13 facing the second electrode 15. A small amount of the electrolyte to be tested is then dripped onto the diaphragm 13. Next, the first electrode 12 is placed, and the negative electrode shell 10 is then fastened onto the positive electrode shell 18. Finally, the entire device is connected to a testing instrument for testing. The overall device structure is simple. By setting an annular insulating layer 14 on the side of the diaphragm 13 facing the second electrode 15, and ensuring that the outer diameter of the annular insulating layer 14 is greater than or equal to the outer diameter of the diaphragm 13, the annular insulating layer 14 can block particle transmission through the edges of the first electrode 12 or the second electrode 15. Current can only be transmitted through the central circular area defined by the annular insulating layer 14, thus forcibly regulating the current line distribution. Within the central circular region, the first electrode 12 and the second electrode 15 are parallel and opposite each other, making the current lines approximately perpendicular and uniformly distributed. The difference in current density from the center to the edge is minimized, eliminating the edge effect caused by three-dimensional diffusion and path length differences, thus allowing for accurate measurement results. Furthermore, since the diaphragm 13 is a non-woven fabric diaphragm with a porous and tortuous structure, it can extend the diffusion path and relaxation time of lithium ions. This makes the overall measurement process closer to the ideal "semi-infinite diffusion" model in electrochemical theory. In this case, the voltage-time curve becomes easier to measure and analyze, allowing for a more accurate and convenient application of Fick's diffusion law to fit and calculate the effective diffusion coefficient of ions in the electrolyte, further improving the measurement results.

[0044] According to some embodiments of this application, such as Figure 1 As shown, the electrolyte diffusion coefficient testing device also includes an elastic element 17, which is disposed between the second electrode 15 and the positive electrode shell 18.

[0045] In this embodiment, the elastic element 17 can refer to something that can deform under the action of external force and return to its original shape after the external force is removed. The elastic element 17 can be elastically compressed in the direction from the negative electrode shell 10 to the positive electrode shell 18. The elastic element 17 can be made of metal or non-metal, such as a leaf spring, a coil spring, a gas spring, a rubber spring, etc. The specific material can be determined according to the actual situation. This embodiment of the specification does not limit this.

[0046] In this embodiment, elastic force is provided by elastic element 17, so that the components between negative electrode shell 10 and positive electrode shell 18 can fit tightly together.

[0047] According to some embodiments of this application, one end of the elastic member 17 facing the positive electrode shell 18 is snapped into the positive electrode shell 18.

[0048] In this embodiment, a buckle, a slot, or other structure may be provided on the side of the positive electrode shell 18 facing the elastic member 17; this is not limited here.

[0049] In use, by snapping the end of the elastic element 17 toward the positive electrode shell 18, the elastic element 17 can be stably positioned inside the positive electrode shell 18, thus preventing the elastic element 17 from shaking during use.

[0050] According to some embodiments of this application, such as Figure 1 As shown, the electrolyte diffusion coefficient testing device also includes a first conductive sheet 11 and a second conductive sheet 16. The first conductive sheet 11 is disposed between the negative electrode shell 10 and the first electrode 12, and the second conductive sheet 16 is disposed between the second electrode 15 and the elastic member 17. In this way, by filling the corresponding accommodating space with the first conductive sheet 11 and the second conductive sheet 16, the various components within the accommodating space can be tightly fitted together.

[0051] According to some embodiments of this application, the first conductive sheet 11 is a rigid conductive sheet, and / or the second conductive sheet 16 is a rigid conductive sheet.

[0052] In this embodiment, only the first conductive sheet 11 may be a rigid conductive sheet, or only the second conductive sheet 16 may be a rigid conductive sheet, or both the first conductive sheet 11 and the second conductive sheet 16 may be rigid conductive sheets. For ease of explanation, the following description will use the example of both the first conductive sheet 11 and the second conductive sheet 16 being rigid conductive sheets.

[0053] Since both the first conductive sheet 11 and the second conductive sheet 16 are rigid conductive sheets, and rigid conductive sheets have high compressive strength and strong support, setting both the first conductive sheet 11 and the second conductive sheet 16 as rigid conductive sheets can improve the support of the corresponding components in the accommodating space and effectively resist the influence of external vibration during the test.

[0054] According to some embodiments of this application, when the inner diameter of the negative electrode shell 10 is smaller than the inner diameter of the positive electrode shell 18, the diameter of the diaphragm 13 is smaller than the inner diameter of the negative electrode shell 10, and the diameter of the diaphragm 13 is larger than the diameter of the first electrode 12.

[0055] For example, when the inner diameter of the negative electrode shell 10 is 22mm and the inner diameter of the positive electrode shell is 24mm, the diameter of the diaphragm 13 can be 20mm and the diameter of the first electrode 12 can be 19mm. Of course, it is understood that the dimensions of the above components can also be other, which is not limited here.

[0056] This ensures the stability of the diaphragm 13's position during the packaging process, preventing the edges of the diaphragm 13 from curling due to pressure from the snap-fit ​​structure during packaging, which would cause the electrochemical test results to deviate from the theoretical value.

[0057] According to some embodiments of this application, the thickness of a single layer in the diaphragm 13 is greater than 100 μm, and the total thickness of the diaphragm 13 is greater than 400 μm and less than 800 μm. It is understood that the thickness of a single layer in the diaphragm 13 could also be 110 μm, etc., and this is not limited here. This avoids the total thickness of the diaphragm 13 being too low, which would prevent the ion diffusion process from being accurately captured by electrochemical signals, thus affecting the measurement results.

[0058] According to some embodiments of this application, the porosity of the nonwoven membrane is 30%-45%. Since the porosity varies greatly between different batches of membranes, it affects the ion transport rate within the porous membrane, making direct comparison of data obtained from different experiments impossible. By limiting the porosity, large differences in ion transport rates within the porous membrane are avoided.

[0059] According to some embodiments of this application, such as Figure 1 As shown, the positive electrode shell 18 has a recessed portion 181 on the side facing the negative electrode shell 10. When the negative electrode shell 10 and the positive electrode shell 18 are fastened together, the side of the negative electrode shell 10 away from the positive electrode shell 18 is located in the recessed portion 181. In this way, the negative electrode shell is prevented from protruding from the recessed portion, and the overall device is small in size.

[0060] According to some embodiments of this application, the annular insulating layer 14 is bonded to the side of the diaphragm 13 facing the second electrode 15.

[0061] The annular insulating layer 14 in this embodiment can be referred to the description above, and will not be repeated here.

[0062] In this embodiment, the annular insulating layer 14 is bonded to the diaphragm 13, thereby facilitating the connection between the annular insulating layer 14 and the diaphragm 13.

[0063] The diffusion coefficient of the electrolyte is calculated using Fick's law and Nernst's equation. The specific calculation formula is as follows: Where D is the diffusion coefficient of the electrolyte. L is the distance (cm) between the two planar electrodes, τ is the porosity of the porous membrane, and k is the slope value during the relaxation process when the logarithm of voltage is linearly related to time. Theoretically, it should conform to the following formula: Where E is the open-circuit voltage of the test structure and t is the relaxation time. In the process of analyzing and fitting the voltage-time Et curve obtained from the test, a correction voltage b is introduced to make... linear fit At its maximum, the slope k calculated at this point is substituted into the formula. The liquid phase diffusion coefficient was calculated.

[0064] In traditional Based on linear fitting, a correction voltage b is introduced to form... An improved fitting model was developed. The linear fit was improved by optimizing the correction voltage b. By reaching the maximum value, a more accurate slope k value can be obtained, thereby improving the accuracy and reliability of diffusion coefficient calculation.

[0065] Example 1 (1) The structural components of the device are as follows: CR2430 negative electrode shell Rigid guide pad, 20mm in diameter, 0.4mm thick. Lithium metal electrode, 19mm in diameter, 0.5mm thick. The diaphragm has a diameter of 20 mm, a porosity of 45%, a thickness of 0.10 mm, consists of 4 layers, and a total thickness of 0.4 mm. Annular insulating layer, inner diameter 14mm, outer diameter 20mm Lithium metal electrode, 19mm in diameter, 0.5mm thick. Rigid guide pad, 20mm in diameter, 0.4mm thick. Elastic element, 20mm in diameter CR2430 positive electrode shell (2) Assemble the button structure in sequence, add 150μL of the electrolyte to be tested inside, and seal it with a press. (3) Connect the button unit to an external electrochemical testing device and polarize it at a potential step of 50mV for 10min at 25℃. (4) Stop polarization and record the voltage-time (Et) curve of the relaxation phase using an external electrochemical device; (5) Linear fitting is performed using the relaxation period of 200s-600s. During the fitting process, a correction voltage b is introduced to make the linear fit more stable. linear fit At its maximum, the slope k calculated at this point is substituted into the formula. The diffusion coefficient was calculated by substituting τ=4, k=-0.004070, and L=0.4mm. The calculated diffusion coefficient of the electrolyte at 25℃ was: The complete data is shown in the table below:

[0066] Example 2 (1) The structural components of the device are as follows: CR2430 negative electrode shell Lithium metal sheet, 19mm in diameter, 0.5mm thick. Porous PP membrane, 20mm diameter, 65% porosity, 0.15mm thickness, 4 layers, total 0.6μm. Circular insulating adhesive, inner diameter 14mm, outer diameter 20mm Lithium metal electrode, 19mm in diameter, 0.5mm thick. Stainless steel gasket, 20mm in diameter, 0.4mm thick. Shrapnel, 20mm in diameter CR2430 positive electrode shell (2) Assemble the button structure in sequence, add 150μL of the electrolyte to be tested inside, and seal it with a press. (3) Connect the button test unit to an external electrochemical test device, test at 35°C, and pass through a potential step polarization of 50mV for 10min. (4) Stop polarization and record the voltage-time (Et) curve of the relaxation phase using an external electrochemical device. (5) Linear fitting is performed using the relaxation period of 100s-500s. During the fitting process, a correction voltage b is introduced to make the linear fit more stable. linear fit At its maximum, the slope k calculated at this point is substituted into the formula. The diffusion coefficient was calculated by substituting τ=1.8, k=-0.005347, and L=0.6mm. The calculated diffusion coefficient of the electrolyte at 35℃ was: The complete data is shown in the table below:

[0067] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of this application, and not to limit them. Although this application has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features therein. These modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of this application, and they should all be covered within the scope of the claims and specification of this application. In particular, as long as there is no structural conflict, the various technical features mentioned in the embodiments can be combined in any way. This application is not limited to the specific embodiments disclosed herein, but includes all technical solutions falling within the scope of the claims.

Claims

1. An electrolyte diffusion coefficient testing device, characterized in that, include: The negative electrode shell, the first electrode, the separator, the annular insulating layer, the second electrode, and the positive electrode shell; The negative electrode shell and the positive electrode shell are fastened together to form a receiving space. The first electrode, the diaphragm, and the second electrode are sequentially disposed in the receiving space along a first direction, wherein the first direction is the direction from the negative electrode shell to the positive electrode shell. The annular insulating layer is disposed on the side of the diaphragm facing the second electrode, and the outer diameter of the annular insulating layer is greater than or equal to the outer diameter of the diaphragm; The diaphragm is a nonwoven diaphragm with a porous tortuous structure, configured to extend the diffusion path and relaxation time of lithium ions.

2. The electrolyte diffusion coefficient testing device according to claim 1, characterized in that, The electrolyte diffusion coefficient testing device also includes an elastic element; The elastic element is disposed between the second electrode and the positive electrode shell.

3. The electrolyte diffusion coefficient testing device according to claim 2, characterized in that, The end of the elastic element facing the positive electrode shell is engaged with the positive electrode shell.

4. The electrolyte diffusion coefficient testing device according to claim 2, characterized in that, The electrolyte diffusion coefficient testing device also includes a first conductive sheet and a second conductive sheet. The first conductive sheet is disposed between the negative electrode shell and the first electrode, and the second conductive sheet is disposed between the second electrode and the elastic member.

5. The electrolyte diffusion coefficient testing device according to claim 4, characterized in that, The first conductive sheet is a rigid conductive sheet, and / or the second conductive sheet is a rigid conductive sheet.

6. The electrolyte diffusion coefficient testing device according to any one of claims 1 to 5, characterized in that, When the inner diameter of the negative electrode shell is smaller than the inner diameter of the positive electrode shell, the diameter of the diaphragm is smaller than the inner diameter of the negative electrode shell, and the diameter of the diaphragm is larger than the diameter of the first electrode.

7. The electrolyte diffusion coefficient testing apparatus according to any one of claims 1 to 5, characterized in that, The thickness of a single layer in the diaphragm is greater than 100 μm, and the total thickness of the diaphragm is greater than 400 μm and less than 800 μm.

8. The electrolyte diffusion coefficient testing device according to any one of claims 1 to 4, characterized in that, The porosity of the nonwoven membrane is 30%-45%.

9. The electrolyte diffusion coefficient testing device according to any one of claims 1 to 4, characterized in that, The positive electrode shell has a concave portion on the side facing the negative electrode shell. When the negative electrode shell and the positive electrode shell are fastened together, the side of the negative electrode shell away from the positive electrode shell is located in the concave portion.

10. The electrolyte diffusion coefficient testing device according to any one of claims 1 to 4, characterized in that, The annular insulating layer is bonded to the side of the diaphragm facing the second electrode.